"dy\/dx + (x\/1-x^2)y = x\u221ay" ---(1)
"y(0)=1" ---(2)
Dividing (1) by "\\sqrt y" we get;
"(1\/\\sqrt y)dy\/dx + (x\/(1-x^2))\\sqrt y = x"
which is a standard Bernoulli's Differential equation which solved in the following standard manner:
Substitute "\\sqrt y=t \\implies 1\/(2\\sqrt y)*dy\/dx=dt\/dx" we get;
"dt\/dx+ tx\/(2(1-x^2)) = x\/2"
which is of the form : "dt\/dx+tP(x)=Q(x)"
whose solution is given as : "t(IF)=\\int Q(IF)dx" where "IF=e^{\\int Pdx}"
Here, "P(x)=x\/(2(1-x^2)); Q(x) = x\/2"
Thus, "IF=e^{\\int xdx\/(2(1-x^2))}=e^{\\int 2xdx\/(4(1-x^2))}"
"=e^{-(ln(1-x^2))\/4}=(1-x^2)^{-1\/4}"
Thus the solution is :
"t(1-x^2)^{-1\/4}=\\int xdx\/(2(1-x^2)^{1\/4})=\\int 2xdx\/(4(1-x^2)^{1\/4})"
Put "1-x^2=u \\implies -2xdx=du" ;we get;
"t(1-x^2)^{-1\/4}=-\\int du\/(4u^{1\/4})=(-1\/3)u^{3\/4}+c"
Putting t and u back; we get;
"\\sqrt y(1-x^2)^{-1\/4}=-(1-x^2)^{3\/4}\/3+c"
Using (2) we get;
"1\/(1-0)=-1\/3+c \\implies c=4\/3"
"\\implies \\sqrt y(1-x^2)^{-1\/4}=-(1-x^2)^{3\/4}\/3+4\/3"
b) given : "-dm\/dt=km" where k is a constant of proportionality and m is moisture content at time t
Solving we get; "m=m_oe^{-kt}; m_0" = moisture content at t=0
Also given : "m(1 hr.)=m_0e^{-k}=m_0\/2\\implies k=ln2"
To find: t for which "m(t)=0.05 m_0=m_0e^{-kt} \\implies kt=ln20"
Thus, "t=ln20\/ln2=0.301 hr."
Comments
Leave a comment